Positive Aspect of Virtual Hotel Operator - I Dewa Gde Satrya (Yayasan Ilomata, 2023)
Traveling is becoming easier with technology. Tourists can choose and determine the accommodation used to stay. Virtual hotel operators (VHO) help travelers choose lodging according to time, cost and desired location. The aim of this research is to describe the advantages of VHO based on family traveler experiences. The growth of tourist accommodation provides choices that benefit tourists. Every accommodation definitely has a market segment. The formulation of the problem in this research is, what are the advantages of VHO based on the experience of family travelers?. This research was conducted using a qualitative approach. The primary data source was obtained through the experience of family travelers staying at VHO (OYO and RedDoorz) in 3 cities (Solo, Jogja and Jakarta). VHO’s advantages mainly lie in its location close to the main tourist destinations and affordable prices. Because of these two things, several things that are lacking from VHO do not reduce satisfaction and positive impressions from tourists. Some things are lacking, such as the accommodation environment being less than beautiful, no parking area, lack of privacy.